Death during recovery from severe malnutrition and its possible relationship to sodium pump activity in the leucocyte. Issue 6068 (23rd April 1977) - Patrick, J
Abstract : The leucocyte data on four malnourished children who died suddenly when high-energy feeding was started were retrospectively analysed. The pretreatment rate constant for sodium efflux in leucocytes was higher and the intracellular sodium concentration lower in this group than in 13 malnourished children who recovered uneventfully with feeding. Two other children with unusual leucocyte electrolyte values and sodium pump activity were identified and closely monitored when high-energy treatment was begun. They rapidly developed the syndrome of extracellular fluid overload but were successfully treated with diuretics and digoxin. Though the precise relation between the findings in the leucocytes and the development of this overload syndrome is not clear, the pretreatment leucocyte values are nevertheless valuable in predicting which malnourished children are at risk of sudden death when refeeding is started.